2002
DOI: 10.1002/aqc.522
|View full text |Cite
|
Sign up to set email alerts
|

An analysis in support of sediment quality thresholds for polycyclic aromatic hydrocarbons (PAHs) to protect estuarine fish

Abstract: Under the US Endangered Species Act and the Essential FishHabitat provisions of the Sustainable Fisheries Act, it is the responsibility of the National Marine Fisheries Service (NMFS) to safeguard the health of fish in estuarine and coastal waters.2. This includes assessment of the impacts of exposure to toxic chemicals on fish and their critical habitat.3. This analysis was conducted to assist NMFS resource managers in determining when fish are exposed to potentially harmful concentrations of one of the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 56 publications
0
33
0
1
Order By: Relevance
“…The study of English sole was particularly interesting because it showed that sole, which are used as indicators of sediment contamination, spend less time at contaminated sites than had been presumed. This suggests that contaminated sediments may have larger impacts on fi sh health than has been previously calculated (Johnson et al 2002 ;Moser et al 2010 ).…”
Section: Other S Peciesmentioning
confidence: 41%
“…The study of English sole was particularly interesting because it showed that sole, which are used as indicators of sediment contamination, spend less time at contaminated sites than had been presumed. This suggests that contaminated sediments may have larger impacts on fi sh health than has been previously calculated (Johnson et al 2002 ;Moser et al 2010 ).…”
Section: Other S Peciesmentioning
confidence: 41%
“…Contaminant states can be measured in biota as exposure, or concentration of contaminant residues in tissues, presence of contaminant metabolites or toxicopathic disease. Contamination of sediments and water are also often measured as a proxy for biota-exposure, based on known or surmised bioconcentration or bioaccumulation factors (e.g., see Johnson et al 2002).…”
Section: State and Impact In The Ecosystemmentioning
confidence: 99%
“…More target PAHs were completely or nearly completely degraded (>90%). The concentration of PAHs in treated sediment was lower than 1000 ng/g, a sediment quality guideline suggested to protect fish against several important health effects (Johnson et al, 2006). Besides, the control experiment of PAHs without persulfate at elevated temperature showed insignificant PAH degradation, as PAHs were extremely stable to chemical and thermal stress.…”
Section: Effect Of Temperature On Pah Removalmentioning
confidence: 95%